Dakwah Komunikatif Bagi Generasi Muda - Muhammad Ali Mada; Mohammad Salehuddin (JDARISCOMB: Jurnal Komunikasi dan Penyiaran Islam, 2026)
Digital disruption has reshaped how Generation Z consumes religious messages, requiring da'wah strategies that are more communicative, contextual, and rooted in local culture. This study addresses a gap in prior research, which has largely examined the technical packaging of digital da'wah content and audience gratification without addressing how Generation Z verifies fragmented short-form religious content, or how local-wisdom-based da'wah translates into measurable offline religious behavior. Using a qualitative approach with a systematic literature review (SLR) design, this study synthesizes ten accredited articles published between 2020 and 2026, selected through a staged screening process: from 1,250 initially identified articles, narrowed to 150 after title-abstract screening, and finalized to 10 through full-text eligibility review based on topical relevance, methodological quality, and contextual recency for Indonesian da'wah. The findings show that effective digital da'wah strategies combine short-form visual content, storytelling rooted in local wisdom such as regional idioms and historical narratives (e.g., the Wali Songo tradition), and interactive features on TikTok, Instagram, and YouTube. Local wisdom functions as a cultural filter that plausibly reinforces Generation Z's sense of identity, although this pattern remains a qualitative indication rather than a measured outcome. Persistent challenges include low digital literacy, message fragmentation, and limited self-verification capacity among young audiences. This study proposes a tentative synthesis framework linking digital content strategy, local cultural narrative, and critical digital literacy, and recommends further empirical research on verification mechanisms and the long-term impact of digital da'wah on real-world religious behavior.